IMMATURE PLATELET FRACTION (IPF) EXAMINATION IN DENGUE FEVER: LITERATURE REVIEW - Indarwati, Uli Masuliyah; Hayati, Defi Nurul (STIKES Syedza Saintika Padang, 2025)
Dengue Fever occurs in patients with varying degrees of severity. One of the symptoms that may appear is thrombocytopenia, which is characterized by a low platelet count. Therefore, it requires special attention in laboratory examinations. The Immature Platelet Fraction (IPF) is one of the hematology test parameters that has potential as a supporting parameter for platelet examination. Evaluation of the IPF value in laboratory tests contributes to the differential diagnosis of thrombocytopenia cases. The purpose of this literature review is to identify the IPF examination in laboratory and to describe the IPF profile in DHF cases. The search method was conducted through PubMed, Google Scholar, and Scopus, with articles reviewed from the years 2016 to 2025. Based on the literature review, IPF examination can be performed using a hematology analyzer. The IPF parameter has an inverse relationship with the platelet parameter increase in IPF value occurs alongside a decrease in platelet count.Conclusion: The IPF parameter can be considered a supporting parameter for platelet examination, for monitoring the severity of thrombocytopenia, and as a predictor of platelet recovery